The Effects of Price-Comparison Advertising on Buyers’ Perceptions of Acquisition Value, Transaction Value, and Behavioral Intentions - Grewal, Dhruv; Monroe, Kent B.; Krishnan, R. (Journal of Marketing, 1998)
The authors expand and integrate prior price-perceived value models within the context of price comparison advertising. More specifically, the conceptual model explicates the effects of advertised selling and reference prices on buyers’ internal reference prices, perceptions of quality, acquisition value, transaction value, and purchase and search intentions. Two experimental studies test the conceptual model. The results across these two studies, both individually and combined, support the hypothesis that buyers’ internal reference prices are influenced by both advertised selling and reference prices as well as the buyers’ perception of the product's quality. The authors also find that the effect of advertised selling price on buyers’ acquisition value was mediated by their perceptions of transaction value. In addition, the effects of perceived transaction value on buyers’ behavioral intentions were mediated by their acquisition value perceptions. The authors suggest directions for further research and implications for managers.